‘This is Not the Holy Land’: Gendered Filipino Migrants in Israel and the Intersectional Diversity of Religious Belonging - Jackson, Vivienne (Religion & gender, 2013)
Social research has highlighted the positive outcomes of religious faith and practice for integration and belonging amongst migrants of different genders. However narratives of Filipino migrants in Israel suggest that religion, gender and belonging may not go hand-in-hand. By applying Anthias’ intersectional framework of ‘translocational positionality’, a wider range of religious faith can be taken into account beyond gendered patterns amongst participants and activists in religious communities. Religious belief and gender intersect with other social locations, leading to the expression of complex orientations to belonging: where people believe they fit into the social order. Going beyond the categories of religion and gender to take in other intersections is essential in understanding the experiences of “non-organised” believers - and non-believers - as well as active religious participants.